Taxonomic revision of Peliosanthes bakeri and P. violacea (Asparagaceae), with description of two new species from Bangladesh and India - Tanaka, Noriyuki (Phytotaxa, 2018)
Syntypes of Peliosanthes bakeri and four varieties (var. clarkei, var. minor, var. princeps and var. violacea) of P. violacea were reexamined to review their identities. As a result, it turned out that the syntypes of P. bakeri comprise two species, P. griffithii and P. subspicata sp. nov., and those of P. violacea include at least six species, P. griffithii, P. khasiana sp. nov., P. macrostegia, P. subspicata, P. teta, and P. violacea. The two new species, P. khasiana from NE India and P. subspicata from Bangladesh and NE India are described and illustrated. The other four species recognised are taxonomically revised as to their identity, circumscription and distribution. In this connection, lectotypes for five taxa are designated. An identification key for the six species recognised is also provided.